Online Class Alert System (OCAS) - Salem, Mohya' Adean Atiya (2009)
Mobile technologies are rapidly growing, and they play an important role in the management of relations between people in social, economic, education, and everyday life. The study aims to improve communication method between lecturer and students by designing a web-based system to help lecturer and students to get news about the new events. Charging scheme for SMS is out of the study scope. The study aims to provide an effective utilization of WEB technology for easing and improving process of communication and alerting between the lecture and students. The prototype of Online Class Alert System (OCAS) is introduced to be used by lecturers at UUM. The system covers two main functions: First function is to review classes and groups of the lecturer, and second is to send SMS to students. The General Methodology of Design Research is adopted to achieve the research objectives. Results of user evaluation on the MBTS indicate that it has good usability in terms of Usefulness, Ease of Use and Outcome and Future Use. An independent samples t-test was conducted to compare the Usefulness, Outcome and Future Use and Ease of Use for participants who send SMS hourly and daily. The t-test results indicate that there is no statistically significant different in the mean Usefulness, Outcome, or Future Use, and Ease of Use on two groups of participant who send SMS or Email, hourly and daily.